2013
DOI: 10.4269/ajtmh.13-0113
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Evidence of Trichostrongylus colubriformis and Trichostrongylus axei Infections in Humans from Thailand and Lao PDR

Abstract: Abstract. Human trichostrongylosis has been reported in Thailand. Recent reports in Lao People's Democratic Republic concerning species identification urged us to investigate species distribution in Thailand. We report eight human cases in Thailand and Lao People's Democratic Republic that were found to be infected by Trichostrongylus colubriformis and T. axei identified and confirmed by molecular techniques. This evidence is the first molecular evidence of human T. colubriformis and T. axei infection in Thail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 12 publications
(12 reference statements)
1
32
0
1
Order By: Relevance
“…In the recent study, the authors reported the occurrence of natural human infection by T. longispicularis for the first time in the world [6]. Also, T. colubriformis was predominant among Trichostrongylus species infecting humans in Thailand [38], France [39] and Laos [4,8]. This may be due to high prevalence of this species in herbivorous animals and also its high zoonotic potential [2].…”
Section: Discussionmentioning
confidence: 99%
“…In the recent study, the authors reported the occurrence of natural human infection by T. longispicularis for the first time in the world [6]. Also, T. colubriformis was predominant among Trichostrongylus species infecting humans in Thailand [38], France [39] and Laos [4,8]. This may be due to high prevalence of this species in herbivorous animals and also its high zoonotic potential [2].…”
Section: Discussionmentioning
confidence: 99%
“…Microscopybased techniques may also produce false-positive results if strongyle eggs representing non-hookworm genera, for example Oesophagostomum spp. and Trichostrongylus spp., 25,26 or fecal material are mistakenly counted as hookworm eggs.…”
Section: Discussionmentioning
confidence: 99%
“…A single individual harbored trichostrongylids, and human trichostrongylosis has recently been reported in Laotians that were found to be infected by Trichostrongylus colubriformis , identified and confirmed by molecular techniques [ 17 , 18 ]. This helminthiasis is contracted by a close contact with farm animals.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, apart from those parasites above, some other rare zoonotic helminthiases were also reported in Lao PDR, e.g., capillariasis ( Capillaria philippinensis ) from fresh water fish [ 14 ], echinostomiasis ( Echinochasmus japonicus ) from fresh water fish and aquatic animals [ 15 ], paragonimiasis ( Paragonimus spp.) from freshwater crab or prawn [ 16 ], trichinellosis ( Trichinella spiralis ) from pigs [ 5 ], and trichostrongyliasis ( Trichostrongylus colubriformis ) from the livestock [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%